Improvement of machinability of hard to machine materials by cryogenic cooling and job preheating - Amin, A. K. M. Nurul; Ismail, Ahmad Faris (IIUM Press, 2009)
This paper presents the impacts of applications of cryogenic and plasma preheating used separately and in combination on chatter and machinability of stainless steel during turning. An effective cryogen delivery system was developed to supply liquid nitrogen. The low temperature of liquid nitrogen could effectively bring down the chip temperature close to embrittlement temperature for better chip breakage and effectively cool the tool to reduce wear rates. An adapted TIG setup was used as the heat source to preheat the workpiece. Preheating improved the elasticity of the work material,stabilized the chip formation process and absorbed vibrations due to higher damping capacity the work piece. Combination approach was an attempt to combine cryogenic cooling and TIG pre-heating techniques to derive the advantages from both approaches in terms of better chip breakability, better chip flow, lower chatter and tool wear and better surface finish.